The Effect of Workload and Physical Facility Infrastructure on the Performance of Security Personnel - Kemala Widya Paramita; Ratri Wahyuningtyas; Fariz (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the effect of workload and physical facility infrastructure on the performance of security personnel at DEF University using a quantitative approach based on the Job Demands-Resources Model. Data were collected from 176 respondents (56.2% of 313 personnel) using a 37-item questionnaire based on SWAT and CPTED, and analyzed via PLS-SEM with 5,000 bootstrap iterations. The results show that infrastructure has a dominant effect (β=0.682; p<0.001) on performance, while workload is not significant (β=-0.115; p=0.074), confirming a significant buffering effect (β=-0.214; p=0.010). These findings suggest prioritizing investments in surveillance technology and communication systems as a strategy to mitigate extreme workload, with managerial implications including a roadmap for enhancing job resources to ensure sustainable campus security performance.